Treatment for Childhood Apraxia of Speech: Past, Present, and Future. - Maas, Edwin (Journal of Speech, Language & Hearing Research)
Purpose: The purposes of this review article were to provide an introduction to and "bird's-eye" overview of the current evidence base for treatment of childhood apraxia of speech (CAS), identify some gaps and trends in this rapidly growing literature, and formulate some future research directions, in order to advance the evidence base and clinical practice for children with CAS. Method: Following a brief introduction outlining important concepts, a narrative review of the CAS treatment literature is provided, and trends and future directions are identified based on this review. The review is organized around four fundamental treatment research questions: (a) "Does Treatment X work?", (b) "Does Treatment X work better than Treatment Y?", (c) "For whom does Treatment X work?", and (d) "What does 'work' mean, anyway?" Results: A wide range of CAS treatments with varying degrees of evidence for efficacy exists. Research is beginning to emerge that compares different treatments and seeks to determine optimal treatment parameters. Few studies to date have explored child-level predictors of treatment response, and the evidence base currently is limited in scope with respect to populations and outcomes studied. Conclusions: A growing evidence base supports the efficacy of a number of treatments for CAS. However, many important gaps in the literature were identified that warrant redoubled and sustained research attention. Research is beginning to emerge that addresses treatment optimization, comparison, candidacy, and outcomes. Suggestions for future research are offered, and the concept of a hypothesized pathway was applied to CAS to illustrate how components of an intervention can effect change in a clinical goal and can help guide development and refinement of treatments for children with CAS.